Hyperhemolysis Syndrome without Underlying Hematologic Disease - Lauren Anne Eberly; Diaa Osman; Nathaniel Perryman Collins (Case Reports in Hematology)
Introduction. Hyperhemolysis is characterized by a life-threatening hemolytic transfusion reaction, with hemoglobin (Hb) and hematocrit (Hct) dropping markedly lower than before transfusion. This phenomenon, commonly described in sickle cell disease, is a rare occurrence in patients without hemoglobinopathies. Case Report. A 55-year-old male presented to the hospital after a motorcycle crash and received 10 units of cross-matched blood for active bleeding. The patient was blood group O, with a negative antibody screen. Ten days later, he represented complaining of dyspnea and was found to have a hematocrit of 12%. The direct antiglobulin test was positive for anti-immunoglobin G and complement. Indirect antiglobulin test was positive for anti-Jka alloantibodies. The presence of Jka antigen was revealed in one unit of previously transfused blood; patient’s RBCs were negative for the Jka antigen. Laboratory data demonstrated findings consistent with DHTR, as well as reticulopenia and elevated ferritin levels. He continued to show signs of active hemolysis, requiring a total of 4 subsequent units of pRBCs. Each transfusion precipitated a drop in Hb and Hct to levels lower than before transfusion; once transfusions were held, the patient slowly recovered. Discussion. Hyperhemolysis in the setting of a DHTR can occur in patients without hematologic disease.